Time frequency analysis of patent ductus arteriosus disease in dogs - (:unkn) unknown (WYDAWNICTWO SIGMA-N O T SP Z O O, 2012)
This study is based on the analysis of the heart sound signals taken from different auscultation areas of three dogs diagnosed with Patent Ductus Arteriosus (PDA). The analyses were started by introducing the mathematical substructure of the methods used. Then the phonocardiographic signals taken from the three dogs were assessed in terms of time-amplitude (t-a) and frequency amplitude (f-a); subsequently, the components of the signals in time-frequency dimensions were examined. As a result of these analyses, the importance of the auscultation area and time-frequency examination in the diagnosis of the PDA disease was demonstrated.
Keywords: Patent Ductus Arteriosus; Heart sounds; Spectrogram